Gendered youth transitions to adulthood in the Drylands: Implications for targeting - Njuguna-Mungai, Esther; Sivi-Njonjo, Katindi; Nchanji, Eileen Bogweh (International Crops Research Institute for the Semi-Arid Tropics, 2019)
Presented on 19 December 2019 by Esther Njuguna-Mungai (CGIAR Research Program on Grain Legumes and Dryland Cereals), Ms. Katindi Sivi-Njonjo (GLDC Affiliated PhD student) and Dr. Eileen Bogweh Nchanji (International Center for Tropical Agriculture / CIAT) as part of the webinar 'Gendered youth transitions to adulthood in the Drylands: Implications for targeting'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Grain Legumes and Dryland Cereals.